Mechanical Performance and Freeze–Thaw Durability of Expansive Clay Stabilized with Graphene Oxide and Fly Ash: A Laboratory Study (Journal of Civil Engineering Researchers, 2025)
Expansive clay soils are characterized by their high water affinity and significant volume changes, which frequently result in structural issues such as swelling, settlement, and cracking, particularly under freeze–thaw (F–T) conditions. This study investigates a dual-stabilization method using fly ash (FA: 5–15%) and graphene oxide (GO: 0.05–0.15%) to enhance the mechanical strength and durability of such soils. After 28 days of curing, samples underwent 3, 6, and 9 F–T cycles, followed by unconfined compressive strength (UCS) testing. Results show that the GO–FA combination significantly improved soil performance, with the optimal mix (10% FA + 0.1% GO) achieving a 76% increase in UCS at zero cycles and reducing strength loss after nine cycles by over 45% compared to untreated soil. These outcomes demonstrate the promise of GO–FA stabilization as a sustainable and effective solution for expansive soils in cold-region geotechnical engineering.
Keywords: Expansive Clay; Freeze–Thaw Cycles; Graphene Oxide; Fly Ash; Soil Stabilization